TSA-MS characterization and kinetic study of the pyrolysis process of various types of biomass based on the Gaussian multi-peak fitting and peak-to-peak approaches - Janković, Bojan; Manić, Nebojša; Stojiljković, Dragoslava; Jovanović, Vladimir (Fuel (Guildford), 2018)
[Display omitted] •Pyrolysis of five different biomasses was studied by STA-MS in dynamic conditions.•Effects of biomass species and heating rates on pyrolysis behaviors were evaluated.•Gaseous products and bio-char yields were analyzed.•Kinetic parameters are derived from substantial properties of pyrolysis rate curves.•Biomass structure plays an important role in pseudo-components decomposition. Slow pyrolysis characterization and kinetic modeling study of five different biomasses (corn brakes (CB), wheat straw (WS), hazelnut shell (HS), sawdust (Beech), and sawdust chemically treated (SDCT)) were performed in this work, using STA-MS techniques. Thermal decomposition of these samples was divided into three stages corresponding to removal of water, devolatilization, and formation of bio-char. Mass spectrometry (MS) showed that H2, CH4, H2O, CO2 (C3H8), CO, and C2H6 were the main gaseous products released during the pyrolysis of biomasses. It was found that H2O, CO and CO2 evolutions for all biomass samples arise from lignin source in biomass, followed by the cellulose, and hemicelluloses. It was established that the pseudo-component fraction estimated by the theoretical calculations is dependent on the heating rate. Using Gaussian multi-peak fitting and peak-to-peak approaches, regardless of the type of biomass, it was found that decomposition of lignin occurs independently of decomposition of remaining two pseudo-components and that there is no interaction between them. Namely, it was assumed that during pyrolysis process of biomasses, carbohydrate (hemicelluloses + cellulose)—lignin chemical structures most likely exist, where the variety of lignin structure units in different types of biomass affects on the level of energy required for its decomposition.